Use of Fourier Transform Infrared Spectroscopy for Monitoring the Shelf Life and Safety of Yogurts Supplemented With a Lactobacillus plantarum Strain With Probiotic Potential - Papadopoulou, Olga S.; Argyri, Anthoula A.; Kounani, Varvara; Tassou, Chrysoula C.; Chorianopoulos, Nikos (Frontiers in Microbiology, 2021)
The aim of the current study was to explore the performance of a probiotic Lactobacillus strain as an adjunct culture in yogurt production and to assess Fourier Transform Infra-Red (FTIR) spectroscopy as a rapid non-invasive analytical technique to evaluate the quality and the shelf life of yogurt during storage. In this respect, bovine milk (full-fat) was inoculated with the typical yogurt starter culture without (control case) or with the further addition of Lb. plantarum T571 as an adjunct (probiotic case). The milk was also inoculated with a cocktail mixture of three strains of L. monocytogenes in two different initial levels of inoculum, and the fermentation process was followed. Accordingly, yogurt samples were stored at 4 and 12 °C and microbiological, physicochemical, molecular and sensory analyses were performed during storage. Results showed that the lactic acid bacteria exceeded 7 log CFU/g during storage in all samples, where the probiotic samples displayed higher acidity, lower pH and reduced counts of L. monocytogenes, in shorter time period than the control ones at both temperatures. Pulsed Field Gel Electrophoresis verified the presence of the probiotic strain until the end of storage at both temperatures and in adequate amounts, while the survival and the distribution of Listeria strains depended on the case. The sensory evaluation showed that the probiotic samples had desirable organoleptic characteristics, similar to the control. Finally, the spectral data collected from the yogurt samples during storage were correlated with microbiological counts and sensory data. Partial Least Squares and Support Vector Machine regression and classification models were developed to provide quantitative estimations of yogurt microbiological counts and qualitative estimations of their sensory status, respectively, based on FTIR fingerprints. The developed models exhibited a satisfactory performance and the acquired results were promising for the rapid estimation of the microbiological counts and sensory status of yogurt.